2017
DOI: 10.1136/gutjnl-2017-314178
|View full text |Cite
|
Sign up to set email alerts
|

Functional imaging and circulating biomarkers of response to regorafenib in treatment-refractory metastatic colorectal cancer patients in a prospective phase II study

Abstract: ObjectiveRegorafenib demonstrated efficacy in patients with metastatic colorectal cancer (mCRC). Lack of predictive biomarkers, potential toxicities and cost-effectiveness concerns highlight the unmet need for better patient selection.DesignPatients with RAS mutant mCRC with biopsiable metastases were enrolled in this phase II trial. Dynamic contrast-enhanced (DCE) MRI was acquired pretreatment and at day 15 post-treatment. Median values of volume transfer constant (Ktrans), enhancing fraction (EF) and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 33 publications
4
71
0
Order By: Relevance
“…In conclusion, our study integrated the innovative biomarker approaches of functional imaging and genomics, which contributed to better prognostication, as recently seen for patients with metastatic melanoma 37 and colorectal cancer. 38 Combining different predictive and prognostic biomarker strategies could help to overcome the inter-and intrapatient heterogeneity of CRPC, thus improving patient risk stratification and treatment selection. A larger prospective evaluation is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our study integrated the innovative biomarker approaches of functional imaging and genomics, which contributed to better prognostication, as recently seen for patients with metastatic melanoma 37 and colorectal cancer. 38 Combining different predictive and prognostic biomarker strategies could help to overcome the inter-and intrapatient heterogeneity of CRPC, thus improving patient risk stratification and treatment selection. A larger prospective evaluation is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Common concerns about trials mandating research biopsies include the lack of patient understanding about the purpose of such studies, and the potential risks associated with additional interventional procedures within the research protocols [18][19][20][21]. In the case of our PROSPECT-C trial [1,2], patients included could already access anti-EGFR antibody treatment via the cancer drug fund (CDF) independent of the research biopsy findings, which meant that the research biopsies were of no direct patient benefit. In order to ensure that patients clearly understood the purpose of their participation in PROSPECT-C and other research studies, a prospective patient based survey at the RM was performed.…”
Section: Discussionmentioning
confidence: 99%
“…PROSPECT-R (clinical trials.gov number [NCT03010722],) [1] were reviewed by the National Research Ethics Committee (NRES) in the UK.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, early HFSR following sorafenib treatment in HCC has been associated with improved treatment response [106]. Importantly, because these events are observed retrospectively, this approach does not inform the pretreatment selection of patients most likely to benefit from regorafenib, and identification of baseline predictive biomarkers is ongoing [107] (see Markers of regorafenib activity).…”
Section: Hfsr and Outcomesmentioning
confidence: 99%
“…As aforementioned, TTP in RESORCE did not differ between RECIST v1.1 and mRECIST, highlighting the need to develop better tools to capture treatment benefit. However, recent studies suggest that imaging techniques may predict response to regorafenib, and this represents an area of active research [107,[115][116][117]. Some studies have shown that small changes in tumor density and size or early cavitation of lung metastases could predict response to regorafenib [115][116][117].…”
Section: Predictive Markers Of Regorafenib Activitymentioning
confidence: 99%